Sub topics
-Differentiation by first principles
-Techniques of differentiation
-First and second derivatives
-Implicit differentiation
-Application of differentiation
DIFFERENTIATION BY FIRST PRINCIPLE
The concept of differentiation
The gradient of a curve at a given point is defined as the gradient of the tangent to the curve at that point and is given by the change of y with respect to x.
As B A
The gradient of the chord AB
The gradient of a tangent AT at point A
Or
Line gradient of chord AB = gradient of tangent AT
Example
Find the gradient of the curve
y = 2x2+ 5
Solution
At point Q
y + y = 2 [x+ x]2 +5
=2 [x2+ 2x x+ x2] +5
= 2x2 +4x x + 2 x2 +5…………. (i)
Subtracting y from equation (i)
y + y –y = 2x2 + 4xx + 2 x2 +5 – [2x2 +5]
y = 4xx+ 22……….(ii)
Dividing ii…………. By x
= 4x +2x………….iii…
As x 0, y 0
And
(iii) Becomes
Note: The expression is called derivative of y with respect [w.r.t] to x
The process of finding derivatives is called DIFFERENTIATION.
Example
Differentiate y = x3 +1 with respect to x
Solution
Y +y = [x +x]3 +1
= x3+ 3x2
x + 3xx2+x3+1
Subtracting y
y + y-y = x3+3x2x+3xx2+x3+1 – x3 – 1
y = 3x2x+3x x2+x3
Dividing by x
As x 0, y
= 3x2
Examples
Find the gradients of the following curves
1.) 2x2-1
2.) y =x3-1
Solution
1) 2x2-1
y+y = 2[x +x]2-1
y+y =2 [x2+2x x+x2]-1
y+y = 2x2 +4x x+x2-1…………(i)
Subtracting y from(i)
y + y – y = 2x2 + 4xx + x2 – 1 – [ 2x2-1]
y = 2x2+ 4xx+2x2-1-2x2+1 ………………..(ii)
Dividing …..(ii) by x
=4x + 2 ………(iii)
As
(iii) Becomes
= 4x
1. y = x3 – 1
Solution
Subtracting y
y + y-y = x3 + 3x 2 + 3xx2 +x3-1-x3 +1
y =3x2x+ 3x+x3
Dividing by
=
= 3x2 + 3x + x2
As ,
= 3x2
EXERCISE
Find the gradients of the following curves.
1.) y = x2
Solution
y + 2
= x2 + 2x + x2
Subtracting y
y + y-y= x2 + 2x + x2 -x2
y = 2x + x2
Dividing by
= 2x +
As
= 2x
2.) y= x3
Solution
y + x = (x + )3
= x3 + 3x2 + 3x2 + x3…….(i)
Subtracting y
y + y-y=X3 + 3x2 x + 3xx2 + x3 – x3
y= 3x2x + 3xx2 + x3………….(ii)
Dividing by x
=
= 3x2 + 3xx + 2
As x 0 , 0 , =
x2
3.) y = x
solution
y + x = x + x………….(i)
subtracting y
y + y-y= x + x – x
y= x ………..(ii)
Dividing by x
1
4.) y =3x2
Solution
y + x = 3 [x +x] 2
=3 [x2+ 2x x +x2]
=3x2+6x x+3x2 -3x2……….(i)
Subtracting y
y + y-y= 3x2+6xx+3x2-3x2
y= 6xx+3x2…….(ii)
Dividing by x
=
As x 0, y 0, =
5.) y = x2 +3x
Solution
y +x = [x+x]2 + 3[x+x]
x2+2xx+ x2+ 3x+3x…………i
Subtracting y
y + y-y = X2 + 2xx+ x2+3x +3x -(x 2 + 3x)
y = 2xx + x2 + 3x……..ii
Dividing by x
= 2x +x +3
As x →0,y → 0, →
2x +3